Design and Development of a 2D Game with Unity: Guess and Match Profession Pictures Quiz in English “Guess Me, Bunny!” - Elistatia, Usi; Permatasari, Sisca (Gameology and Multimedia Expert, 2025)
Learning English is a form of self-development that can help enhance critical thinking skills and broaden cultural insights. A vast amount of information, including scientific research, books, articles, and online resources, is available in English. Mastering this language provides access to a broader spectrum of knowledge. However, learning English is often considered very challenging for some individuals due to differences in language structure, pronunciation, intonation, and cultural aspects. Developing an educational English language game serves as a tool to spark interest in learning the language based on these challenges. This study aims to increase enthusiasm for learning English, improve retention and understanding, and promote engaging contextual learning strategies. A qualitative research method is used in this study. The ADDIE approach is applied in the design process. The outcome of this research is an online educational game application for learning English, titled “Guess Me, Bunny!”. This program serves as a teaching tool, fostering curiosity and facilitating children's English language development.